The WTO Doha Round, Cotton Sector Dynamics and Poverty Trends in Zambia - Balat, Jorge F.; Porto, Guido G. (World Bank, Washington, DC, 2012)
The Zambian cotton sector went through significant reforms during the 1990s. After a long period of parastatal control, a process of liberalization in cotton production and marketing began in 1994. These reforms were expected to benefit agricultural farmers. In Zambia, these are rural, often vulnerable, smallholders. The authors investigate the connection between the dynamics of the cotton sector and the dynamics of poverty and evaluate to what extent cotton can work as a vehicle for poverty alleviation. They find that cotton can indeed act as an effective mechanism for increased household welfare. They also find income gains associated with cotton production, as well as positive impacts on the long-run nutritional status of Zambian children. The impacts, however, are relatively small.